STRATEGI PENGEMBANGAN PERIKANAN CAKALANG YANG BERBASIS DI PELABUHAN PERIKANAN TIPE D KABUPATEN ACEH BARAT, PROVINSI ACEH - Hafinuddin Hafinuddin; Sri Resti; Zuriat Zuriat (JURNAL PERIKANAN TROPIS, 2018)
Skipjack tuna fishery have significant contribution for production of capture fisheries at West Aceh, Aceh province. Based on that, this research aims to formulate development strategy of skipjack tuna fishery based on type D fishing port at West Aceh District. This research is using qualitative approach, where collecting data method is using survey method and purposive sampling was used for collecting data technique. Analysis hierarchy process (AHP) was used to analysis data. The result show that increasing capital for fishermen is main objective to achieve skipjack tuna fishery development. Then, fisheries business actor has strategic role for skipjack tuna fishery development. As for a scenario to develop skipjack tuna fishery is to enhance capacity of fuel station for fishermen and ice plant that is in type D fishing port. Result of this study will be expected to be consideration for fishery stakeholders in developing skipjack tuna fishery at West Aceh District and that is can improving welfare of the skipjack tuna fishermen.